2009
DOI: 10.1016/j.matbio.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dermal elastic fibers in the absence of fibulin-5 reveals potential roles for fibulin-5 in elastic fiber assembly

Abstract: Fibulin-5 is a 66 kDa modular, extracellular matrix protein that localizes to elastic fibers. Although in vitro protein-protein binding studies have shown that fibulin-5 binds many proteins involved in elastic fiber formation, the specific role of fibulin-5 in elastogenesis remains unclear. To provide a more detailed analysis of elastic fiber assembly in the absence of fibulin-5, the dermis of wild-type and fibulin-5 gene knockout (Fbln5 −/− ) mice was examined with electron microscopy (EM). Although light mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 63 publications
6
39
1
3
Order By: Relevance
“…Consistent with our previous studies (19,28), V3 expression by ASMCs significantly increased mRNA levels of tropoelastin as well as fibulin 5, a component of microfibrils critical in elastic fiber formation (Fig. 1, A and B) (22)(23)(24). Fibulin 1 and fibrillin 1 mRNA levels did not differ between V3-expressing ASMCs and control ASMCs (data not shown).…”
Section: V3 Expression Enhances Elastic Fiber Formation and Mrna Exprsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our previous studies (19,28), V3 expression by ASMCs significantly increased mRNA levels of tropoelastin as well as fibulin 5, a component of microfibrils critical in elastic fiber formation (Fig. 1, A and B) (22)(23)(24). Fibulin 1 and fibrillin 1 mRNA levels did not differ between V3-expressing ASMCs and control ASMCs (data not shown).…”
Section: V3 Expression Enhances Elastic Fiber Formation and Mrna Exprsupporting
confidence: 91%
“…Previously, we have demonstrated that expression of the V3 isoform of versican in ASMCs generates an ECM enriched in elastic fibers and that this ECM had reduced capacity to bind monocytes (4,18,19,28). We now show a causal relationship between changes in elastin accumulation and monocyte adhesion such that knocking down tropoelastin or fibulin 5, a component of microfibrils critical for elastic fiber formation (22)(23)(24), partially reverses the inhibition of monocyte adhesion caused by V3 expression. in control and V3-expressing ASMCs cultured for 7 days was detected at mRNA (A) and protein (B) levels using real-time PCR and Western blotting as described under "Materials and Methods."…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, the elastic fibers in the mutant skin are notably shorter, particularly in the dermis between hair follicles. Electron microscopic analyses indicate that ultrastructural abnormalities of the elastic fibers in Fbln4 E57K/E57K mice resemble those previously seen in the fibulin-5 null mouse skin (33). These include an elastin core consisting of small globules with low electron density, disconnection between small elastin aggregates and microfibrils, and an excess of microfibrils without an elastin core.…”
Section: Discussionmentioning
confidence: 51%